Fruit Waste Management through Vermicomposting: the Case of PRAN, Bangladesh - Ibrahim, Abu Shahadat Md; Mohammad, Ashif; Nuruzzamal, Md; Shams, S. M Nasif (Formosa Journal of Applied Sciences, 2024)
PRAN, situated in Natore, Bangladesh, operates a sizable fruit processing facility. This facility processes approximately two hundred seasonal foods and fruit varieties, generating substantial organic waste. The overarching goal is to establish an organic food chain for both the national and international markets, thereby contributing to the mitigation of Bangladesh's emerging energy and fertilizer crisis. The vermicomposting method was employed, and the experiment was conducted on a miniature scale over 90 days. A dedicated setup was constructed to yield three metric tons of monthly fertilizer. Upon completion of the experiment, the output fertilizer underwent rigorous testing in the laboratory. The results indicated that the component ratios were well-suited for application in agricultural lands. This research marks a significant step towards sustainable waste management and the development of a valuable resource for the agricultural sector in the region.